2019
DOI: 10.3233/blc-180182
|View full text |Cite
|
Sign up to set email alerts
|

Thermo Reversible Hydrogel Based Delivery of Mitomycin C (UGN-101) for Treatment of Upper Tract Urothelial Carcinoma (UTUC)

Abstract: Background: There is an unmet need for an effective local treatment of upper tract urothelial carcinoma (UTUC). Drug delivery to the pyelocaliceal system and pursuant efficacy of intracavitary therapy is limited by urine production that washes the drug away, shortening dwell time and direct contact with the urothelium. Successful endoscopic management is often dictated by lesion size, grade, and focality. A thermo-reversible hydrogel formulation of Mitomycin C (UGN-101, formerly MitoGel) was developed and has … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 19 publications
0
11
0
Order By: Relevance
“…4 Liquid when chilled, UGN-101 is instilled via ureteral catheter or nephrostomy tube and becomes a semisolid gel at body temperature that dissolves during urine production over 4-6 hours, resulting in increased dwell time at the tumor site. 5 We previously reported interim results from OLYMPUS, a phase 3 clinical trial that evaluated UGN-101 for treatment of low-grade UTUC. 6 The trial's primary endpoint was complete eradication of disease in the ipsilateral pyelocalyceal system (defined as negative ureteroscopic evaluation, negative cytology, and negative for-cause biopsy) 4-6 weeks following 6 weekly induction instillations of UGN-101.…”
Section: Introductionmentioning
confidence: 99%
“…4 Liquid when chilled, UGN-101 is instilled via ureteral catheter or nephrostomy tube and becomes a semisolid gel at body temperature that dissolves during urine production over 4-6 hours, resulting in increased dwell time at the tumor site. 5 We previously reported interim results from OLYMPUS, a phase 3 clinical trial that evaluated UGN-101 for treatment of low-grade UTUC. 6 The trial's primary endpoint was complete eradication of disease in the ipsilateral pyelocalyceal system (defined as negative ureteroscopic evaluation, negative cytology, and negative for-cause biopsy) 4-6 weeks following 6 weekly induction instillations of UGN-101.…”
Section: Introductionmentioning
confidence: 99%
“…The effectiveness of intravesical therapy is dependent on high drug concentration and dwell time to maximize exposure to the bladder mucosa. 2…”
mentioning
confidence: 99%
“…22 With mitomycin thermal gel, which requires 6 weekly catheter-based instillations, events such as acute kidney injury (9%), myelosuppression (9%), ureteral stricture preventing further instillations (5%), and treatment discontinuation (27%) were described in the original report in which a 36% CR rate was seen. 23 In the Phase 3 trial of primary chemoablation with mitomycin thermal gel for low-grade UTUC (OLYMPUS), a 59% CR rate was seen, while 44% of patients developed ureteric stenosis. 24 Our study demonstrated similar efficacy, in both low- and high-grade tumors, with no cases of treatment-related ureteral stricture.…”
Section: Discussionmentioning
confidence: 99%